Metabolic biomarkers mediate allergic rhinitis via circulating inflammatory proteins: Evidence from a Mendelian randomization study - Xiang Cao; Boyang Zhang; Wei Wang; Zijiao Xu; Zhixin Jiang (Brazilian Journal of Otorhinolaryngology)
Objective: Allergic Rhinitis (AR), a prevalent allergic condition, markedly diminishes quality of life and increases public health burdens. This study investigated the mediating roles of Metabolic Biomarkers (MBs) in the associations between Circulating Inflammatory Proteins (CIPs) and AR, aiming to uncover novel therapeutic targets. Methods: Utilizing Mendelian Randomization (MR), we leveraged genetic variants as instrumental variables to delineate causal relationships between CIPs and AR. Data were extracted from comprehensive Genome-Wide Association Studies (GWAS). A two-sample MR approach was employed to assess both the direct and mediated effects of CIPs on AR through MBs. Inverse-Variance Weighting (IVW) served as the main analytical method, supplemented by rigorous sensitivity analyses to confirm the robustness of the findings. Results: Our analysis revealed that specific CIPs like C-C motif Chemokine-19 (CCL19), Notch-like Epidermal growth factor-related Receptor (DNER), and Interleukin-6 (IL-6) significantly elevate the risk of AR, whereas Interleukin-10 (IL-10) exhibit protective properties. Key MBs, notably Adenosine 5'-Monophosphate (AMP) to urate ratio, plasma lactate, and N-acetylputrescine, played critical roles in mediating these relationships, indicating their potential as therapeutic targets. Conclusion: This investigation highlights the pivotal role of MBs in modulating the influence of CIPs on AR. The insights gained from this study not only deepen our understanding of AR pathophysiology but also open new avenues for metabolic intervention in its treatment. Level of evidence: In terms of level of evidence, MR studies are second only to randomized controlled trials.